2019
DOI: 10.1038/s41467-019-10375-x
|View full text |Cite
|
Sign up to set email alerts
|

APC/CCDH1 synchronizes ribose-5-phosphate levels and DNA synthesis to cell cycle progression

Abstract: Accumulation of nucleotide building blocks prior to and during S phase facilitates DNA duplication. Herein, we find that the anaphase-promoting complex/cyclosome (APC/C) synchronizes ribose-5-phosphate levels and DNA synthesis during the cell cycle. In late G 1 and S phases, transketolase-like 1 (TKTL1) is overexpressed and forms stable TKTL1-transketolase heterodimers that accumulate ribose-5-phosphate. This accumulation occurs by asymmetric production of ribose-5-phosphate from the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 55 publications
0
57
0
1
Order By: Relevance
“…Proteomics data indicated increased TKT levels in SARS-CoV-2-infected cells, suggesting a role is played by the non-oxidative PPP. Notably, activity of the non-oxidative PPP may not always be a direct consequence of available TKT levels, as TKT activity can be strongly increased by heterodimer formation with transketolase-like 1 (TKTL1) [ 18 ]. However, anti-SARS-CoV-2 effects exerted by the TKT inhibitor BOT suggest that TKT and the non-oxidative PPP are functionally involved in SARS-CoV-2 replication.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics data indicated increased TKT levels in SARS-CoV-2-infected cells, suggesting a role is played by the non-oxidative PPP. Notably, activity of the non-oxidative PPP may not always be a direct consequence of available TKT levels, as TKT activity can be strongly increased by heterodimer formation with transketolase-like 1 (TKTL1) [ 18 ]. However, anti-SARS-CoV-2 effects exerted by the TKT inhibitor BOT suggest that TKT and the non-oxidative PPP are functionally involved in SARS-CoV-2 replication.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this TKTL1 enables the production of Acetyl-CoA, a central metabolic building block for lipids. Recently, it has been demonstrated that TKTL1 controls cell cycle [12]. Upregulation of TKTL1 is associated with poor prognosis in colon and urothelial cancer as well as rectum and lung carcinoma [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A study published in 2019 revealed the regulation mechanism of pentose phosphate-related metabolism in tumour cells, which targets the adjustment of the tumour's cell cycle, affecting the energy requirement of tumour cells [38] . Other studies pointed out that ribosomes involved in epithelial-mesenchymal transition accelerate the metastasis of cancer cells [39] and that chemokines have a regulatory role in immune cell recruitment and tumour and stromal cell biology [40] .…”
Section: Discussionmentioning
confidence: 99%